Acciones de adaptación al turismo: la creación de un nuevo espíritu de capitalismo en el Valle del Colca (Arequipa, Perú) (2015)
The article uses an interdisciplinary perspective to analyze the creation of a new spirit of capitalism. This is put in evidence trough institutional documents analysis, historic contextualization and the characterization of the adaptive dynamics of actors, under the frame of national policies, programs and projects for tourism development. The main findings, at the exploratory level, show the responses of the actors and the logics to which their actions correspond, taking into account what happened in Colca Valley (Arequipa, Peru) around tourism and their desires of entering in the market, diversify their economies as well as to participate in development projects.